THE EFFECT OF ANESTHESIA OF BASIL (Ocimum basilicum) LEAF EXTRACT WITH DIFFERENT DOSES ON THE SURVIVAL OF CATFISH (Pangasius sp.) - Faqihudin, M. Syukron; Hidayati, Sri; Aji, Muhammad Tri (Asian Journal of Aquatic Sciences, 2023)
The purpose of this study was to determine the effect of anesthesia of basil leaf extract with different doses on the survival of striped catfish. This research was conducted in Kedungsari Village, North Magelang District, Magelang City, Jawa Tengah in January 2022. The study was carried out using a Completely Randomized Design (CRD) with 3 treatments and 4 replications. The treatments were anesthesia with doses of 10%, 15%, and 20%, the catfish that had fainted was put in Styrofoam for 7.5 hours. The variables observed included the duration of anesthesia, the duration of fainting, the length of recovery time, and survival. The results showed that the dose of basil leaf extract had the best concentration of basil leaf extract, which was 20% with 2.5 minutes of stunning time, 25.74 minutes of fainting time, and 6.13 minutes of recovery time. The highest survival rate of catfish using basil leaf extract was found at a concentration of 20%, 15% while the lowest survival rate was at a concentration of 10% treatment.